Discovery service as one stop information services - Abdullah, Sarifah (2014)
Libraries spent million ringgit annually for purchasing and subscribing information resources (books, journals, multimedia, online databases, etc.). These resources can be accessed through library portal and online catalog. However, the usage statistic shown that it is not very cost effective. With the advent of Internet and Google, many professors and students gravitate to Google as gateway to research. Due to this, the libraries have to change their approach in providing information access to users. Instead of bewildering users with a bevy of specialized databases—books here, articles there—many libraries are bulldozing their digital silos. They now offer one-stop search boxes that comb entire collections like Google style by using discovery tools. Among discovery tools available in the market are: EBSCO Discovery Service; Summon; Primo and WorldCat Discovery Services. This paper will discuss on the features, strength and benefits to the library as one stop information services.